WORK-INTEGRATED LEARNING IN MASS COMMUNICATION EDUCATION: A CRITICAL EVALUATION USING FINK’S TAXONOMY - Dr. Mona Gupta (Glocalism: Journal of Culture, Politics and Innovation, 2025)
The Bachelor of Arts in Journalism and Mass Communication (Bajmc) program can be termed as professional or vocational course systematically designed to make students industry ready by inculcating specialised knowledge and training along with building practical skills. The syllabus caters to diverse subjects and has integrated the element of internships, workshops and certifications. The following research is conducted with a purpose to evaluate the integration of Work-Integrated Learning (Wil) in Mass Communication Education through the Bachelor of Arts in Journalism and Mass Communication (Bajmc) program at Guru Gobind Singh Indraprastha University using Dee Fink’s Significant Learning Taxonomy and the Work-Integrated Learning Curriculum Classification (Wilcc) Framework. Hybrid Analytical Approach is used which combines both quantitative and qualitative analysis. The objectives of the syllabus are reviewed using Dee Fink’s taxonomy, defined into clusters by Wilcc framework and are assessed on the basis of credit weightage. Faculty interviews conducted for understanding the delivery of the content from work integrated perspective are analysed using thematic analysis. The result shows the strong presence of foundational as well implementation of practical knowledge. The syllabus has the flexibility to strategically cater to real-world projects and students taking free lancing projects leading to their holistic development. However, the curriculum lacks professional and embedded Wil demands improvement and requires workplace exposure to promote coordinated co-curricular activities. Fink’s taxonomy can be a guiding template for creating a comprehensive skill spectrum and using Wilcc framework can be vital for aligning the credit-based subjects with the industry standards and working systems and can stimulate students for the dynamic media industry. Regular assessment considering the Wilcc framework can be crucial for aligning credit-bearing subjects with the workplace engagements.